Optimization of ultra-high performance concrete, quantification of characteristic features. Issue 1 (1st January 2019) - Chen, Yang; Matalkah, Faris; Soroushian, Parviz; Weerasiri, Rankothge; Balachandra, Anagi
Abstract: An optimization experimental program was designed to identify a desired balance of key mix design parameters for an economical ultra-high-performance concrete (UHPC) mixture. The following mix design parameters were evaluated: superplasticizer content, coarse-to-fine aggregate ratio and steel fiber volume fraction. The values of packing density, water film thickness and excess paste film thickness were calculated considered in the optimization experimental program. The trends in the effects of packing density, water film thickness and excess paste film thickness on compressive strength and fresh mix flow were investigated. The results were used to identify viable ranges of these defining characteristics for the category of UHPC. Response surface analysis of the fresh mix flow and the hardened concrete compressive strength test results led to identification of the optimum values of mix design parameters. The optimum mix was found to produce a desired balance of fresh mix flow and hardened concrete compressive strength.